2023
DOI: 10.1038/s41375-023-01816-0
|View full text |Cite
|
Sign up to set email alerts
|

Disruption to the FOXO-PRDM1 axis resulting from deletions of chromosome 6 in acute lymphoblastic leukaemia

Abstract: A common problem in the study of human malignancy is the elucidation of cancer driver mechanisms associated with recurrent deletion of regions containing multiple genes. Taking B-cell acute lymphoblastic leukaemia (B-ALL) and large deletions of 6q [del(6q)] as a model, we integrated analysis of functional cDNA clone tracking assays with patient genomic and transcriptomic data, to identify the transcription factors FOXO3 and PRDM1 as candidate tumour suppressor genes (TSG). Analysis of cell cycle and transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…However, there are many causes of night sweats that are unrelated to cancer. Sinclair, P. B., et al [46] has identified the red blood cells supply oxygen to all cells in the body. The author says that when these cells are deficient, symptoms such as headaches can occur.…”
Section: B Analysis Based On Symptomsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are many causes of night sweats that are unrelated to cancer. Sinclair, P. B., et al [46] has identified the red blood cells supply oxygen to all cells in the body. The author says that when these cells are deficient, symptoms such as headaches can occur.…”
Section: B Analysis Based On Symptomsmentioning
confidence: 99%
“…That would be a really bad sweat. This causes patients to become drenched in water Sinclair, P. B., et al [46] The red blood cells supply oxygen to all cells in the body. The author says that when these cells are deficient, symptoms such as headaches can occur Gupta, K., et al [47] If your red blood cell count is low enough to be pale, you will have more congestion.…”
Section: B Analysis Based On Symptomsmentioning
confidence: 99%